Ratio of T-helper type 1 (Th1) to Th17 cytokines in whole blood is associated with human β-defensin 3 expression in skin and persistent staphylococcus aureus nasal carriage - Nurjadi, Dennis; Kain, Marlon Shiva; Marcinek, Patrick; Gaile, Marika; Heeg, Klaus; Zanger, Philipp (The journal of infectious diseases, 2016)
Background. Nasal colonization has gained attention as an effect modifier in Staphylococcus aureus vaccine trials, suggesting interference of carriage with T-c
Gesehen am 26.06.2020